Laws of the Republic of Uzbekistan As A Source of Land Law - Melitojiyev Muhammadrizo Ulugʻbek oʻgʻli (Western European Studies, 2023)
Since the earliest times of the development of society, land has served as the material basis of land relations and the main source of property
Keywords: Republic of Uzbekistan; effective use; property